Geology Structural Analysis of the Tanjung Betung II Region, Bengkulu: Recognized through Geological Mapping and Lineament Analysis - Sari, Devi Puspita; Sutriyono, Edy (Universitas Negeri Gorontalo, 2024)
The research area is located in the Tanjung Betung II area, North Kaur, Bengkulu. This research was conducted to determine the geological structure and its relationship with the graben system in the Bengkulu basin by identifying and measuring structural components recorded in rock units. In interpreting deformation mechanisms, this research utilizes surface data obtained from geological structure mapping and lineament analysis based on Digital Elevation Model (DEM) images. Field observations on outcrops have identified five types of structures that have a general northwest-southeast trend, hereinafter referred to as the Manau IX fault, Bunian fault, Tanjung Kurung fault, Aek Kule syncline and Padang Manis fault. This structure may be associated with a graben system that formed in the late phase of basin evolution in the Neogene. Importantly, the structures recorded in the outcrop sequence may be the result of tectonic deformation that occurred during the Late Neogene, coinciding with the start of the Barisan orogeny.